2016
DOI: 10.1021/acs.biomac.5b01668
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Design of Ca-Sensitive Paramagnetic Liposomes Results in an Unprecedented Increase in Longitudinal Relaxivity

Abstract: Bioresponsive MRI contrast agents sensitive to Ca(II) fluctuations may play a critical role in the development of functional molecular imaging methods to study brain physiology or abnormalities in muscle contraction. A great challenge in their chemistry is the preparation of probes capable of inducing a strong signal variation that could be detected in a robust way. To this end, the incorporation of small molecular weight bioresponsive agents into nanocarriers can improve the overall properties in a few ways: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Most of the preparation methods of liposomes include the exploitation of potentially toxic solvents such as diethyl ether, methanol, and chloroform (Garello et al 2016). The final product may contain remnants of these toxic solvents chip in potential toxicity and affect the stability of the lipid vesicles.…”
Section: Heating Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the preparation methods of liposomes include the exploitation of potentially toxic solvents such as diethyl ether, methanol, and chloroform (Garello et al 2016). The final product may contain remnants of these toxic solvents chip in potential toxicity and affect the stability of the lipid vesicles.…”
Section: Heating Methodsmentioning
confidence: 99%
“…Other kind of bioactive molecules also could be encapsulated within nanoliposomes via this method regarding their temperature sensitivities. Mozafari et al showed that preparing nanoliposomes via heating method result in none-toxic nanoliposomes to cultured cells, whereas nanoliposomes provided by former prevalent preparation techniques showed substantial levels of cytotoxicity due to using volatile solvents (Garello et al 2016). Producing of nanoliposomes in industrial scales is another important feature of this method.…”
Section: Heating Methodsmentioning
confidence: 99%
“…Typically, these agents are injected intracisternally at concentrations in the low micromolar range. Additionally, several calcium-responsive paraCEST agents have been developed [62], as well as several functional MRI (fMRI) methods using oligomerization/aggregation of calcium-responsive agents [63,64]. These agents remain under use as a research tool only; to our knowledge, there are no active clinical translational approaches underway.…”
Section: Calcium-responsive Contrast Agentsmentioning
confidence: 99%
“…The visualization of membrane potentials by MRI remains a dream today. Calcium detection has been at the center of many studies and important chemistry efforts have been made to develop Ca‐sensitive MRI probes, without successful in vivo translation so far. NTs play a key role in signal transduction and the first NT responsive MRI probes appeared in recent years .…”
Section: Responsive Probesmentioning
confidence: 99%
“…Major biomarkers to give direct information on neural transmission involve membrane potential, calcium ions and NTs. [11] The visualization of membrane potentials by MRI remains ad ream today.C alcium detection has been at the centero f many studies and important chemistry efforts have been made to develop Ca-sensitive MRI probes, [12][13][14] without successful in vivo translation so far.N Ts play ak ey role in signal transduction and the first NT responsive MRI probes appearedi nr ecent years. [15] NTsa re af amily of over one hundred molecules involved in synaptic transmission of very different chemical natures.…”
Section: Mri Detection Of Nt Concentration Changesmentioning
confidence: 99%